Analisis Manajemen Risiko pada Tingkat Kinerja Pelayanan Kapal di PT X - Valdeza, Sandy; Wahyuni, Ajeng Putri Dwi; Febriani, Nadila; Ladesi, Vivian Karim; Sahara, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Loading and unloading activities are the transfer of cargo from ship to port or vice versa. One of the loading and unloading activities is on liquid bulk cargo. Loading and unloading activities are related to ship services, namely ET indicators: BT. One of the indicators is Idle Time (IT). Idle Time (IT) is the number of unused working hours during loading and unloading work time at the mooring. IT value < RKAP indicates minimal obstacles to loading and unloading operations. The purpose of this study is to analyze Idle Time in liquid bulk loading and unloading activities every month and analyze the factors that can affect the performance of liquid bulk loading and unloading in 2021 at Company X. This research uses descriptive quantitative methods. The results of the analysis of Company X, namely Idle Time (IT) are not good because IT> RKAP. There are obstacles in loading and unloading activities due to various factors. The inhibiting factors are tool factors, environmental factors and worker factors. This requires good risk management.